Ultrafast strain engineering and coherent structural dynamics from resonantly driven optical phonons in LaAlO3 - J. R. Hortensius (Nature Portfolio, 2020)
Abstract Strain engineering has been extended recently to the picosecond timescales, driving ultrafast metal–insulator phase transitions and the propagation of ultrasonic demagnetization fronts. However, the nonlinear lattice dynamics underpinning interfacial optoelectronic phase switching have not yet been addressed. Here we perform time-resolved all-optical pump-probe experiments to study ultrafast lattice dynamics initiated by impulsive light excitation tuned in resonance with a polar lattice vibration in LaAlO3 single crystals, one of the most widely utilized substrates for oxide electronics. We show that ionic Raman scattering drives coherent rotations of the oxygen octahedra around a high-symmetry crystal axis. By means of DFT calculations we identify the underlying nonlinear phonon–phonon coupling channel. Resonant lattice excitation is also shown to generate longitudinal and transverse acoustic wave packets, enabled by anisotropic optically induced strain. Importantly, shear strain wave packets are found to be generated with high efficiency at the phonon resonance, opening exciting perspectives for ultrafast material control.